PEDAGOGICAL COMMUNICATION STRATEGIES OF ISLAMIC EDUCATION TEACHERS IN INTERNALIZING ISLAMIC VALUES IN ELEMENTARY SCHOOL STUDENTS - Qonitatun Nisa'; Zaevi Ma’rifah; Rahman Kurniawan (Al-Mudarris: Journal Of Education, 2026)
This study aims to analyze the pedagogical communication strategies of Islamic Education (PAI) teachers in the process of internalizing Islamic values in the moral aspect of students at SDN Jambesari 03 Bondowoso. The study uses a qualitative approach with a case study design to gain an in-depth understanding of pedagogical communication practices in the context of elementary schools. The research subjects included IRE teachers, sixth-grade students, and the principal. Data were collected through non-participatory observation, semi-structured in-depth interviews, and documentation, then analyzed using an interactive analysis model that included data reduction, data presentation, and repeated conclusion drawing. The results of the study indicate that the pedagogical communication strategies of PAI teachers are integrative and relational, combining contextual lectures, interactive dialogues, storytelling of exemplary stories, behavioral habits, and consistent personal exemplary behavior. The process of internalizing values takes place through cognitive, affective, and behavioral stages, reinforced by a religious school culture and the support of the principal's policies. The dynamics of dialogical and supportive pedagogical interactions create a safe psychological atmosphere that encourages the formation of students' internal moral commitment. This study confirms that pedagogical communication functions as an effective medium for value transformation in shaping the character of elementary school students and provides practical implications for strengthening religious character education.